Inovasi Pelayanan Kesehatan dalam Meningkatkan Akses dan Kualitas Layanan di Rumah Sakit Mahulu Pratama Kabupaten Mahakam Ulu melalui Implementasi Aplikasi SIPANDU - Adrianus Gusti Bria; Sri Kamariyah; Nihayatus Sholicah (Journal of Innovative and Creativity, 2025)
This research focuses on innovation in healthcare services through digital technology by utilizing a mobile-based application to facilitate registration, queue management, and access to examination results. Based on Everett Rogers' diffusion innovation theory, this study examines five key indicators: relative advantage, compatibility, complexity, trialability, and observability. The data used in this research includes interviews with hospital staff and users, as well as survey results and observations related to the use of the SIPANDU application at the hospital. The research method used is a qualitative approach with descriptive data analysis. The findings indicate that this application successfully improves efficiency, reduces patient waiting time by 87%, and cuts transportation costs by nearly half. Additionally, the integration of digital medical records increases healthcare worker productivity by 72%. The compatibility of the application with user needs is reflected in the survey results, which show that 93% of registration staff feel the application is easy to use and aligns with their workflow. The conclusion of this study shows that the implementation of SIPANDU has successfully improved access to and the quality of services at Mahulu Pratama Hospital. However, some challenges, such as adjusting users' habits and limitations in covering all types of services, still need to be addressed. Therefore, recommendations for further development include enhancing training for healthcare workers and patients, as well as updating the application interface based on user feedback. By addressing these challenges, the SIPANDU application has the potential to be more widely adopted and have a greater impact on healthcare services in remote areas